PRINSIP-PRINSIP MEMBACA PEMAHAMAN - Djojosuroto, Kinayati (Kajian Linguistik dan Sastra, 2006)
This article discusses some topics about reading comprehension such as the meaning of reading, levels of comprehension, reading process, and micro-skills for reading comprehension. Reading is the activity of perceiving a written text in order to understand its meaning. The understanding of meaning resulted from reading is called reading comprehension, involving three levels: literal, interpretive, and applied. Such meaning can be achieved by top-down, bottom-up, and interactive processing. Besides, the reader should master some micro-skills for reading comprehension, ranging from recognizing a core of words untul developing and using a battery of reading strategis.Â Key words: reading, levels of comprehension, reading process, and micro-skills